2021
DOI: 10.3389/fanim.2021.728635
|View full text |Cite
|
Sign up to set email alerts
|

Improving Beef Progeny Performance Through Developmental Programming

Abstract: Maternal nutritional management during gestation appears to modulate fetal development and imprint offspring postnatal health and performance, via altered organ and tissue development and tissue-specific epigenetics. This review highlighted the studies demonstrating how developmental programming could be explored by beef producers to enhance offspring performance (growth, immune function, and reproduction), including altering cow body condition score (BCS) during pregnancy and maternal supplementation of prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 118 publications
0
10
0
Order By: Relevance
“…Therefore, maternal supplementation of protein and energy during gestation may influence the offspring BW at birth by altering nutrient availability and glucose transfer to the fetus via IGF system regulation ( Sferruzzi-Perri et al, 2006 ). Nonetheless, variable results on offspring birth BW have been reported with nearly half of the studies observing that prepartum supplementation of protein and energy had no effects or increased offspring birth BW by on average 3.2 kg ( Moriel et al, 2021 ). In the present study, birth BW of the first offspring tended to be greater for calves born from 3× and 7× cows (and numerically greater for 1× calves) compared to NOSUP cows and no effects of supplementation frequency were observed for offspring birth BW, corroborating with previous studies ( Klein et al, 2014 ; Moriel et al, 2016a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, maternal supplementation of protein and energy during gestation may influence the offspring BW at birth by altering nutrient availability and glucose transfer to the fetus via IGF system regulation ( Sferruzzi-Perri et al, 2006 ). Nonetheless, variable results on offspring birth BW have been reported with nearly half of the studies observing that prepartum supplementation of protein and energy had no effects or increased offspring birth BW by on average 3.2 kg ( Moriel et al, 2021 ). In the present study, birth BW of the first offspring tended to be greater for calves born from 3× and 7× cows (and numerically greater for 1× calves) compared to NOSUP cows and no effects of supplementation frequency were observed for offspring birth BW, corroborating with previous studies ( Klein et al, 2014 ; Moriel et al, 2016a ).…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent results were also observed for calf preweaning growth, with nearly half of the studies reporting either no effects or increased calf BW at weaning following maternal supplementation of protein and energy during gestation ( Moriel et al, 2021 ). Prepartum supplementation of DDG increased offspring BW at the time of weaning ( Bohnert et al, 2013 ; Kennedy et al, 2019 ; Palmer et al, 2022a ) compared to no prepartum supplementation of DDG.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal supplementation of protein and energy and monensin during gestation influence offspring BW at birth and during preweaning phase, by altering nutrient availability and glucose transfer to the fetus via IGF system regulation ( Kubota et al, 1992 ; Perry et al, 2002 ; Sferruzzi-Perri et al, 2006 ; Sullivan et al, 2009 ). Maternal supplementation of protein and energy during gestation had either no effects or increased offspring birth BW by on average 3.2 kg ( Moriel et al, 2021 ). Subsequent studies, conducted at the same research site as herein, demonstrated that maternal supplementation of DDG at 1 to 2 kg/d (DM basis) during late gestation of beef cows did not impact ( Palmer et al, 2022a ) or increased calf birth BW by 2.9 kg ( Izquierdo et al, 2022 ), but increased calf BW at weaning by 6 to 16 kg ( Izquierdo et al, 2022 ; Palmer et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing body condition score ( BCS ) of beef cows during the third trimester of gestation, via supplementation of energy and protein, provides an opportunity to modulate maternal circulating concentrations of hormones and metabolites essential for fetal growth, such as glucose and insulin-like growth factors 1 ( IGF-1 ) and 2 ( IGF-2 ; Bell et al, 2005 ; Sferruzzi-Perri et al, 2006 ), and enhance subsequent postnatal offspring growth ( Marques et al, 2016a ). The exact outcomes of maternal prepartum supplementation of protein and energy on beef offspring preweaning growth are variable ( Moriel et al, 2021 ) and dependent on multiple factors, including supplementation timing ( Palmer et al, 2022a ), frequency ( Izquierdo et al, 2022 ), carbohydrate type ( Palmer et al, 2022b ), and source of trace minerals source ( Marques et al, 2016b ). Studies evaluating the impacts of adding feed additives, such as ionophores, into prepartum supplementation of beef cows are limited ( Turner et al, 1980 ; Walker et al, 1980 ; Linneen et al, 2015 ), particularly for Bos indicus -influenced beef cows reared in tropical and subtropical environments ( Cooke et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because meat production is linked to animal's muscle growth potential and body composition, and the main events associated to the formation of this tissue occur in the intrauterine period, strategies of maternal supplementation during crucial periods of gestation are consider an important topic of investigation. In a recent review, the effects of maternal protein and/or energy supplementation showed variable effects on offspring's phenotype, possibly due to the divergencies on the duration of supplementation and evaluation period among the studies (Moriel et al, 2021). In-depth studies identified changes in many biological processes related to energy metabolism in the skeletal muscle of the offspring resulting from maternal diet .…”
Section: Chapter 1 1general Introductionmentioning
confidence: 99%